The Influence of Company Size and Company Age on Audit Delay in Banking Companies Listed on the Indonesia Stock - Andrew Patrick Marunduh (ProBisnis : Jurnal Manajemen, 2022)
This study aims to determine: (1 ) Does company size affect audit delay (2) Does company age affect audit delay. (3) Does company size and company age simultaneously affect audit delay.This research uses a quantitative research type with the population taken in this study, namely banking companies listed on the Indonesia Stock Exchange in 2021. The sample selection was carried out by purposive sampling with a total sample of 34 samples. The data analysis technique used is descriptive statistics, multiple linear regression analysis, and classical assumption testing The research results show that (1) company size has a negative effect on audit delay as indicated by the regression coefficient -3.1633 and a significance value of 0.0134. (2) Firm age has a negative effect on audit delay as indicated by the regression coefficient -0.2632 and a significance value of 0.0500. (3) Company size and company age together have an effect on audit delay as indicated by a significance value of 0.001238 and an Adjusted R2 value of 0.3761., Google Trends, Spark AR, Canva, Watsap.id, and Trello. Research will then be done to find out the increase brand awareness of the company through Meta insight.